Characterization of circRNA–miRNA–mRNA networks regulating oxygen utilization in type II alveolar epithelial cells of Tibetan pigs - Yang, Yanan; Li, Yongqing; Yuan, Haonan; Liu, Xuanbo; Ren, Yue; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Molecular Biosciences, 2022)
Understanding the signaling pathway regulatory mechanisms in type II alveolar epithelial (ATII) cells, the progenitor cells responsible for proliferating and regenerating type I alveolar epithelial (ATI) and ATII cells, in Tibetan pigs is beneficial for exploring methods of preventing and repairing cellular damage during hypoxia. We simulated a hypoxic environment (2% O2) for culture ATII cells of Tibetan pigs and Landrace pigs, with cells cultured under normoxic conditions (21% O2) as a control group, and performed integrated analysis of circular RNA (circRNA)–microRNA (miRNA)–messenger RNA (mRNA) regulatory axes by whole-transcriptome sequencing. Functional enrichment analysis indicated that the source genes of the differential expressed circRNAs (DEcircRNAs) were primarily involved in cell proliferation, cellular processes, and cell killing. A series of DEcircRNAs were derived from inhibitors of apoptosis proteins and led to a key autonomous effect as modulators of cell repair in Tibetan pigs under hypoxia. The significant higher expression of COL5A1 in TL groups may inhibited apoptosis of ATII cells in Tibetan pigs under lower oxygen concentration, and may lead their better survive in the hypoxia environment. In addition, a competing endogenous RNA (ceRNA) network of functional interactions was constructed that included novel_circ_000898-ssc-miR-199a-5p-CAV1 and novel_circ_000898-ssc-miR-378-BMP2, based on the node genes ssc-miR-199a-5p and ssc-miR-378, which may regulate multiple miRNAs and mRNAs that mediate endoplasmic reticulum (ER) stress-induced apoptosis and inflammation and attenuate hypoxia-induced injury in ATII cells under hypoxic conditions. These results broaden our knowledge of circRNAs, miRNAs, and mRNAs associated with hypoxia and provide new insights into the hypoxic response of ATII cells in Tibetan pigs.